การสื่อสารอัตลักษณ์และบทบาททางสังคมของลิเกไทใหญ่ - ปรีดาพร ศรีเมือง (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
This qualitative research aimed to study the components, identities and social roles of Shan Opera. Participants were 72 people, including the persons who associated with Shan Opera (n=20), the audiences of Shan Opera (n=50) and the Shan scholars (n=2). Data were collected during October 2015 – March 2017 by in-depth interviews, via 12 Live Shan Opera shows, in Thailand and Myanmar (Shan state), and also via related documents. Data were analyzed by content analysis. The findings revealed that : 1. there were 12 components of Shan Opera covering: 1) process of the show 2) musical instruments and melodies 3) people who involved with the show 4) placement, backdrop and stage 5) Showtime and show opportunities 6) clothes 7) knowledge of Shan Opera 8) prohibitions and superstitions 9) sing in Shan language 10) respect for teachers /masters 11) trust of Goddesses (called Surussavadee) 12) relations between men and women. 2. there were 6 identities of Shan Opera, including: 1) identity of songs 2) identity of local language 3) identity of entertainment 4) identity of Shan costume 5) identity of Local literature and 6) identity of minority nationalism. 3. there were 12 social roles of Shan Opera: 1) role in self-formation 2) role in upgrading individual’s status in society 3) role in self-reflection 4) role in creating memories together 5) role in building up harmonization 6) role in entertaining 7) role in transmitting knowledge 8) role in teaching people to be a good person 9) role in playing as a Cultural Learning Center 10) role in reflecting individual and local identity 11) role in creating campaign and 12) role in connecting with other folk media. .